The Use of Social Media and Media Literacy during the Pandemic in Indonesia - Farida Win Sari Manurung; Winning Amintas Kartika Waruwu; Sukarman Purba; Lambok Pamancar Saragi (International Conference on Multidisciplinary Research, 2022)
The COVID-19 pandemic has brought changes to nearly all aspects, including the aspect of economy and education. The use of social media has then increased during the pandemic for various purposes, such as for doing businesses and learning. However, many people have some constraints when using social media due to poor media literacy, limited knowledge in information and communication technology (ICT), lack of supporting facilities and infrastructure, and poor environmental condition.This study thus aims to describe the trends of social media use during the COVID-19 pandemic and how important digital literacy is to allow users to use social media wisely and carefully. The type of this research is literature review to presents theoretical frameworks to answer the research question. Keyword: learning, the COVID-19 pandemic, online learning media, media online learning